Phase II study of paclitaxel (Taxol) and ifosfamide (Holoxan) in inoperable non-small-cell lung cancer - Thongprasert S. (2014)
A total of 27 patients with advanced previously untreated non-small-cell lung cancer were treated with paclitaxel and ifosfamide. The starting dose of paclitaxel was 175 mg/m2 given for 3 h by intravenous infusion on day 1. Ifosfamide 4 g/m2 was given for 4 h by intravenous infusion on day 2. Dosage of the two drugs was modified according to nadir white blood count after each cycle. Involved in the treatment were 17 males and 10 female patients. The median age was 61 years (range 47-71 years) and the median Karnofsky performance status was 70% (range 60-90%), 13 cases were stage IIIb and 14 cases were stage IV. One case was not evaluable due to lost follow-up after a single dose of chemotherapy. There were five cases not determined due to a timing error. Of 21 evaluable cases, eight achieved partial response (PR 38%, confidence interval 18.1-61.5%), seven achieved stable disease, two had a minor response. The median survival time of the whole group was 255 days (range from 38 to 567 days). The major toxicities were myalgia; arthralgia and neuropathies. Throughout the study, only three cases (15%) were treated at dose level 0. After the first cycle, 18 cases were treated at dose level 1, after a second cycle, 13 cases were treated at dose level 2. Three cases with grade 3 leukopenia were seen at dose level 0. At dose level 1, two cases had grade 3 leukopenia. At dose level 2, four episodes of grade 3 leukopenia were noted. It is concluded that paclitaxel can be combined safely with ifosfamide at these dosage levels. The response rates were comparable to the other chemotherapy combination in advanced non-small-cell lung cancer. The survival results were acceptable and comparable to the cisplatin-containing regimen. This study indicates that combinations of paclitaxel and/or ifosfamide with other agents, such as gemcitabine and vinorelbine, should be explored.